An innovative method for trans-impedance matrix interpretation in hearing pathologies discrimination. (April 2022) - Vozzi, A.; Ronca, V.; Malerba, P.; Ghiselli, S.; Murri, A.; Pizzol, E.; Babiloni, F.; Cuda, D.
Highlights: The study of trans-impedance matrix (TIM) allows for discriminating patients with cochlear implants affected by two different earing pathologies. Trans-impedance matrices (TIMs) of otosclerotic patients presented higher Exponential Decay constant and lower Shannon Entropy compared to patients with congenital hearing loss. Patients with same pathology presented highly correlated trans-impedance matrices (TIMs). The correlation decreased for patients with different pathologies. Otosclerotic patients with cochlear implants presented different patterns of trans-impedances over basal and apical electrodes. Abstract: Trans-impedance measurement is a novel methodology for assessing the positioning of a cochlear implant (CI). This study proposes an innovative use of trans-impedance measurements to characterize specific hearing pathologies by means of the trans-impedance matrix (TIM) quantitative analysis. Three indices are used: Shannon Entropy, the Exponential Decay constant and Spatial Correlation. These indices were computed on the TIMs of two groups of patients, clustered in terms of hearing pathology: (i) congenital hearing loss (CONG) and (ii) otosclerosis (OTO). The study aimed to demonstrate the sensitivity of the above synthetic indices in relation to the considered hearing pathologies. Furthermore, the first two indices were employed to explore the influence of the positioning of the electrode, either over (i) the basal or (ii) the apical regions, on the TIMs patterns. The results suggest that the indices were statistically different for the patient groups and the positioning impacted solely on OTO patients. In particular: (i) CONG patients displayed significantly higher Shannon Entropy ( p  = 0.0002) and (ii) a lower Exponential Decay constant than OTO patients ( p  = 0.001); (iii) the OTO patients exhibited a lower Shannon Entropy and a higher Exponential Decay constant over the basal regions than the apical regions ( p  < 0.008); (iv) Spatial Correlation demonstrated that TIMs had specific patterns according to the hearing pathology ( p  < 0.008).